Probing anomalous top-Higgs couplings at the HL-LHC via H→WW* decay channels. (January 2019) - Liu 刘, Yao-Bei 要北; Moretti, Stefano
Abstract: We study the prospects of probing the anomalous tHq ( q = u, c ) couplings via SS2L or 3L signatures at the High Luminosity (HL-LHC) run of the 14 TeV CERN collider. We focus on signals of the tH associated production followed by the decay modes t → bℓ + νℓ and H → WW *, and t t ¯ production followed by the decay modes t → bℓ + νℓ and t ¯ → H ( → W W ∗ ) q ¯, where ℓ = e, μ . Based on two types of H → WW * decay topologies, one assuming the semileptonic decay mode H → WW *→ ℓ + νjj and the other the fully leptonic decay mode H → W W ∗ → ℓ + ν ℓ − ν ¯, we perform a full simulation for signals and backgrounds. It is shown that, at the future HL-LHC, the branching ratio Br ( t → uh ) ( Br ( t → ch )) can be probed to 1.17 (1.56) × 10 −3 for the same-sign di-lepton channel, and to 7.1 × 10 −4 (1.39 × 10 −3 ) for the 3L channel at 3 σ sensitivity.